2017
DOI: 10.1002/bdra.23589
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of neural tube defects in Lrp2 mutant mouse embryos by folic acid supplementation

Abstract: Background Neural tube defects (NTDs) are among the most common structural birth defects in humans and are caused by the complex interaction of genetic and environmental factors. Periconceptional supplementation with folic acid can prevent NTDs in both mouse models and human populations. A better understanding of how genes and environment interact is critical towards development of rational strategies to prevent NTDs. Low density lipoprotein-related protein 2 (Lrp2) is involved in endocytosis of the folic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…A functionally related gene that also causes exencephaly in mice is Lrp2 , a multi-ligand membrane receptor that seems to mediate uptake of folic acid into cells by Folr1 at the apical surface of the developing neuroepithelium [ 211 ]. Maternal injection with folic acid during early gestation reduces the NTD frequency in Lrp2 mutants by half; dietary supplementation with folic acid is not effective [ 212 ].…”
Section: Folate and Ntdmentioning
confidence: 99%
“…A functionally related gene that also causes exencephaly in mice is Lrp2 , a multi-ligand membrane receptor that seems to mediate uptake of folic acid into cells by Folr1 at the apical surface of the developing neuroepithelium [ 211 ]. Maternal injection with folic acid during early gestation reduces the NTD frequency in Lrp2 mutants by half; dietary supplementation with folic acid is not effective [ 212 ].…”
Section: Folate and Ntdmentioning
confidence: 99%
“…Most of the clinical characteristics seen in patients with LRP2 gene mutations are also present in the LRP2-deficient mouse models (Cases et al, 2015;Hammes et al, 2005;Kur et al, 2014;Sabatino et al, 2017;Spoelgen et al, 2005;Wicher and Aldskogius, 2008). Our report demonstrates that Xenopus is a new valuable model for the functional analysis of Lrp2 deficiency.…”
Section: Conservation Of Lrp2 Function In Disease Etiologymentioning
confidence: 58%
“…Interestingly, LRP2-deficient mice not only suffer from HPE caused by ventral forebrain defects, but also display defects of the anterior dorsolateral neural tube as well as spinal cord anomalies that cannot be explained by loss of SHH signaling in the developing forebrain (Kur et al, 2014;Wicher and Aldskogius, 2008;Ybot-Gonzalez et al, 2002). In previous studies, we and other labs demonstrated that LRP2 null mutants present with a dilated dorsal neural tube and in 38 % of all mice we observed cranial neural tube closure defects (NTDs; Kur et al, 2014;Sabatino et al, 2017). Of note, human LRP2 variants have now also been identified in patients suffering from NTDs, ultimately leading to anencephaly and myelomeningocele (open spina bifida;…”
Section: Introductionmentioning
confidence: 69%
“…Lrp2 −/− mutant mice studied on a C57BL/6N, a mixed C57BL/6N; 129/SvEMS-Ter, CD1, and a C3H/HeNcrl background show fully penetrant forebrain defects and perinatal lethality (Sabatino et al, 2017; Spoelgen et al, 2005; Willnow et al, 1996). We and others previously found that a Lrp2 267/267 ENU mutant line on a predominantly FVB/N background survived to adulthood (Gajera et al, 2010; Zarbalis et al, 2004; Zywitza et al, 2018).…”
Section: Discussionmentioning
confidence: 99%